2022
DOI: 10.1007/s41030-022-00191-y
|View full text |Cite
|
Sign up to set email alerts
|

The Current and Future Role of Technology in Respiratory Care

Abstract: Over the past few decades, technology and improvements in artificial intelligence have dramatically changed major sectors of our day-to-day lives, including the field of healthcare. E-health includes a wide range of subdomains, such as wearables, smart-inhalers, portable electronic spirometers, digital stethoscopes, and clinical decision support systems. E-health has been consistently shown to enhance the quality of care, improve adherence to therapy, and allow early detection of worsening in chronic pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 72 publications
0
5
0
1
Order By: Relevance
“…Data-Driven Decision Making and Adherence Feedback: (18) showed that patients with smart inhalers may now make datadriven decisions regarding their asthma care. Patients got feedback on their compliance and reminders, which made it easier for them to stick to their recommended drug schedules and improved overall illness management (32).…”
Section: Early Exacerbation Detection and Timely Interventionsmentioning
confidence: 99%
“…Data-Driven Decision Making and Adherence Feedback: (18) showed that patients with smart inhalers may now make datadriven decisions regarding their asthma care. Patients got feedback on their compliance and reminders, which made it easier for them to stick to their recommended drug schedules and improved overall illness management (32).…”
Section: Early Exacerbation Detection and Timely Interventionsmentioning
confidence: 99%
“…S6). In addition, real-time feedback of the respiratory rate (RR) of the human body was crucial for medical health monitoring 46 We used a systematic algorithm (see SI.…”
Section: Respiratory Monitoringmentioning
confidence: 99%
“…Kemudian adanya penolakan pasien untuk mengubah pola perawatan yang sudah berlangsung selama ini. Masalah selanjutnya adalah terkait ketidak pastian tanggung jawab klinis untuk meninjau karena monitoring Dewa Ayu: Penggunaan Digital Inhalers (Smart Inhalers) pada Pengelolaan Pasien Penyakit Paru Obstruksi Kronis bersifat jarak jauh (Honkoop et al, 2022). Sehingga diperlukan penelitian yang lebih baik terkait manfaat dan efektifitas digital inhaler terhadap hasil kesehatan untuk pasien PPOK, diharapkan nantinya memberi kepercayaan pada pasien untuk dapat diaplikasikan dalam praktek sehari-hari.…”
Section: Hambatan Dan Tantanganunclassified